2020
DOI: 10.37506/mlu.v20i1.399
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Multidrug Resistant Tuberculosis in Minia, Egypt

Abstract: BackgroundTuberculosis (TB) is a disease of great antiquity and has almost certainly caused more suffering and death than any other infection. A total of 40 patients were registered with a diagnosis of MDR-TB during 2010-2018 in Minia. The majority of patients were from rural areas (27; 67.5%) and male (27; 67.5%). Emergence of MDR-TB has the potential to be a serious public health problem in that necessitates strengthened TB control and improved continuous monitoring of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…No significant difference was found between the two groups in terms of the gender of participants ( p = 0.685 ). However, the male gender was higher in both groups representeing (80%) of DR-TB patients and 66% of DS-TB patients, which aligns with the results reported in several other studies [ 3 , 20 , 21 ]. This matches the epidemiological pattern of tuberculosis as males have more hours of outdoor exposure and usually have more risk factors, such as smoking and alcohol intake.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No significant difference was found between the two groups in terms of the gender of participants ( p = 0.685 ). However, the male gender was higher in both groups representeing (80%) of DR-TB patients and 66% of DS-TB patients, which aligns with the results reported in several other studies [ 3 , 20 , 21 ]. This matches the epidemiological pattern of tuberculosis as males have more hours of outdoor exposure and usually have more risk factors, such as smoking and alcohol intake.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, there was also an insignificant difference between both groups regarding age ( p = 0.414 ). However, the mean age for TB in both groups was similarly reported in other studies [ 20 22 ]. These findings were attributed to the high mobility and social interaction during this reproductive age [ 23 ].…”
Section: Discussionsupporting
confidence: 84%
“…Considering the ratio of infections among males vs females, one study reported that the split between males and females with multi-drug resistant tuberculosis was 70.4% and 29.6% respectively [ 201 ], In a study conducted in patients with resistant tuberculosis in Ghana, the ratio of males and females was 69.6% and 30.4% respectively [ 202 ], whilst in another study conducted in Egypt, the ratio of males and females was reported as 67.5% and 32.5%, respectively [ 203 ]. Moreover, in a similar research work conducted in Ethiopia 65.3% male and 34.7% female has multi drug resistant TB [ 204 ].…”
Section: Discussionmentioning
confidence: 99%